Breastfeeding and long‐term maternal metabolic health in the HUNT Study: a longitudinal population‐based cohort study. (27th December 2018) - Velle‐Forbord, V; Skråstad, RB; Salvesen, Ø; Kramer, MS; Morken, NH; Vanky, E
Abstract : Objective: Breastfeeding (BF) has been reported to improve long‐term maternal metabolic health in observational studies, but not in the randomised controlled PROBIT study. Research also suggests that maternal pre‐pregnant metabolic health may affect BF. We aimed to disentangle effects of BF on long‐term maternal metabolic health from effects of pre‐pregnant metabolic health on BF duration and long‐term metabolic health. Design: Longitudinal population‐based cohort study. Setting: Nord‐Trøndelag county, Norway. Population: Women with a first live‐born baby (1987–2008) participating in the Nord‐Trøndelag Health Study (HUNT). Methods: Odds ratios (ORs) for short BF duration (<3 months) by pre‐pregnant body mass index (BMI), waist circumference (WCF), blood pressures (BPs), and heart rate (HR) were adjusted for age and smoking using logistic regression. Mixed linear models were used to estimate effects of BF duration (<3, 3–6, >6 months) on mean values of metabolic health parameters from baseline to follow‐up. Main outcome measures: Mean change in BMI, WCF, BPs, HR, serum‐glucose, and serum‐lipids from baseline to follow‐up by BF duration categories. Results: We analysed 1403 women with a median follow‐up of 12 years (interquartile range 11–22). Pre‐pregnant WCF and HR correlated inversely with BF duration. Pre‐pregnant BMI had a u‐shaped correlation‐pattern with BF duration. We observed similar between‐group differences in metabolic health parameters at baseline and at follow‐up, which implies that mean change in metabolic health parameters was similar across BF groups. Those women who started out with the best health had the longest BF duration and ended up with the best health, and those women who started out with the poorest health had shortest BF duration and ended up with the poorest health. Conclusions: Our results do not support a causal relationship between long BF duration and improved metabolic health. It is more likely that pre‐pregnant metabolic health affects both BF duration and long‐term metabolic health. Reverse causality can explain previously observed improved long‐term metabolic health after BF. Tweetable abstract: Breastfeeding seems not to affect long‐term maternal metabolic health, but good pre‐pregnant metabolic health does. Tweetable abstract: Breastfeeding seems not to affect long‐term maternal metabolic health, but good pre‐pregnant metabolic health does.